The pathogenesis of Pasteurella multocida local isolates in mice and chicken - ., Supar; Setiadi, Yudi; ., Djaenuri; Kurniasih, Nina; Poerwadhikarta, Bhakti (Indonesian Animal Sciences Society, 2000)
Avian cholera or fowl cholera is a bacterial disease caused by Pasteurella multocida strain of serogroup A, has been recognized as important disease in domestic poultry such as ducks and chicken. P. multocida strains derived from overseas and local isolates are stored as freeze dried and kept at the Research hlstitute for Veterinary Science (BALITVET) culture collection (BCC). Some of those bacteria are still alive and can be used as vaccine candidates. Each strain or isolate was activated in brain heart infusion broth containing foetal calf serum and incubated at 37Â°C then it was identitied by biochemical reactions. Field surveys Were conducted in Central Java and South Kalimantan to observe fowl cholera problems and sample collections for isolation of pathogens. Of the 14 of Pasteurella multocida strains or isolates from BCC, II strains (9 imported 2 local isolates) were still alive. In addition to this 2 isolates trom chicken and duck were viable. Seven out of 9 imported strains killed mice within 3 x 24 hours, similarly for the local isolates (BCC 299, 2331, DYI, DY2, 12TG, 15TG). However, the only BCC 2331 and DY2 isolates were able to kill two week old chicken witIlin 6 x 24 hours post inoculation. From this experiment indicated that the P. multocida local isolates (BCC 2,331 and DY2) are more pathogenic than that of imported strains. Two strains of imported P. multocida BCC 2331, 1362 and 6 local isolates (BCC 299, 2331, DYI, DY2, 12TG and 15TG would be selected for mono- and polyvalent vaccine candidates in the following experiments and the highly patogenic BCC 2331 and DY2 isolates would be used to challenge the vaccinated animals. Â Key words: Pasteurella multocida local isolate, pathogenicity, vaccine against fowl cholera candidate